Avaliação da qualidade do sistema de vigilância da influenza e outros vírus respiratórios com ênfase na região de fronteira: Brasil, 2009-2021 - Leandro, Gustavo Cezar Wagner (2023)
Introduction: Respiratory viruses cause a significant number of infections and deaths around the world each year, in addition to sporadically producing pandemics with high mortality, resulting in an even greater impact on health systems, mainly affecting socially vulnerable, elderly, and immunosuppressed people. The main health actions used for prevention and control are immunization and surveillance, with the surveillance system identifying circulating viruses in good time. However, for surveillance systems to achieve their objectives, it is essential to evaluate the processes carried out. Aim: To assess the quality of the surveillance system for influenza and other respiratory viruses in Brazil between 2009 and 2021. Method: This is a cross-sectional and longitudinal time series study with an ecological approach and an evaluative nature, applied to secondary data from individual records in the Influenza Epidemiological Surveillance Information System. Results: The results were presented in two manuscripts. The first, entitled "Evaluation of the surveillance system for acute respiratory infections: a study of records from Brazil (2009-2021)", presents the epidemiological profile of the 3,398. 492 cases of acute respiratory infection; the temporal distribution of the quality of notifications, with a 34.8% reduction in completeness during the COVID-19 pandemic; the contextual factors associated with quality, with the North and Northeast macro-regions presenting notifications with lower completeness; and the association of the quality of notification with death, with the high completeness of the variables on signs and symptoms and hospital care as a protective factor (OR: 0.559 and 0.906, respectively) and timeliness in communication, sample collection and recording (OR: 0.717, 0.897 and 0.910, in that order). The second manuscript "Evolution of surveillance of acute respiratory infections in Brazil, associated factors and effects of the COVID-19 pandemic: an ecological study (2009-2021)" presents the quality indices of the surveillance system for acute respiratory infections between health regions, identifying spatial clusters of regions with notifications showing high completeness (Moran's I. 0.431) and high timeliness (Moran's I: 0.510) in the south of the country, in contrast to the north: 0.431) and high timeliness (Moran's I: 0.510) in the south of the country, in contrast to the north, being associated with the human development index and availability of hospital beds per inhabitant. Conclusions: The work highlights the crucial role of epidemiological surveillance actions in shaping clinical outcomes at the individual level and that contextual factors are associated with the performance of the surveillance system at the regional level; it also highlights the importance of improving monitoring strategies, especially in lowperforming areas, to strengthen rapid responses to possible outbreaks.